Electrochemical Ammonia Gas Sensing in Nonaqueous Systems: A Comparison of Propylene Carbonate with Room Temperature Ionic Liquids - Ji, X.; Banks, C.; Silvester, Debbie; Aldous, L.; Hardacre, C.; Compton, R. (Wiley - VCH Verlag GmbH & Co. KGaA, 2007)
First, the direct and indirect electrochemical oxidation of ammonia has been studied by cyclic voltammetry at glassy carbon electrodes in propylene carbonate. In the case of the indirect oxidation of ammonia, its analytical utility of indirect for ammonia sensing was examined in the range from 10 and 100 ppm by measuring the peak current of new wave resulting from reaction between ammonia and hydroquinone, as function of ammonia concentration, giving a sensitivity 1.29107 A ppm1 (r2¼0.999) and limit-of-detection 5 ppm ammonia. Further, the direct oxidation of ammonia has been investigated in several room temperature ionic liquids (RTILs), namely 1-butyl-3-methylimidazolium tetrafluoroborate ([C4mim][BF4]), 1-butyl-3-methylimidazolium trifluoromethylsulfonate ([C4mim][OTf]), 1- Ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([C4mim][NTf2]) and 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mim][PF6]) on a 10 mm diameter Pt microdisk electrode. In four of the RTILs studied, the cyclic voltammetric analysis suggests that ammonia is initially oxidized to nitrogen, N2, and protons, which are transferred to an ammonia molecule, forming NHþ4 via the protonation of the anion(s) (A). However, in [C4mim][PF6], the protonated anion was formed first, followed by NHþ4. In all five RTILs, both HA and NHþ4 are reduced at the electrode surface, forming hydrogen gas, which is then oxidized. The analytical ability of this work has also been explored further, giving a limit-ofdetection close to 50 ppm in [C2mim][NTf2], [C4mim][OTf], [C4mim][BF4], with a sensitivity of ca. 6107 A ppm1 (r2¼0.999) for all three ionic liquids, showing that the limit of detection was ca. ten times larger than that in propylene carbonate since ammonia in propylene carbonate might be more soluble in comparison with RTILs when considering the higher viscosity of RTILs.